KARAKTERISASI BIODEGRADASI PADA KOMPOSIT POLYMER POLYLACTID ACID (PLA) DENGAN PENAMBAHAN CHITOSAN DAN HYDROXYAPATITE - Serfandi, Dina Novera; Setyarini, Putu Hadi; Purnami, Purnami; Sulistyono, Sulistyono (Jurnal Rekayasa Mesin, 2023)
Polylactid Acid (PLA) is a biodegradable polymer made from natural ingredients so it is safe to use for biomaterials. The purpose of this study was to determine the biodegradation characteristics of the addition of chitosan powder and Hydroxyapatite to PLA. There were 4 variations in this study, namely PLA 100 (pure PLA), PLA-chitosan-Hydroxyapatite 94-3-3 (Composite 1), PLA-chitosan-Hydroxyapatite 94-0-6 (Composite 2), PLA-chitosan-Hydroxyapatite 94-6-0 (Composite 3). Samples were prepared using the extrusion method to form filaments, then the filaments were injected with a temperature of 170-190°C and an injection pressure of 5-6 bar. Characterization was carried out using the Immerse Test, FTIR Test, and SEM-EDS Test. The results of the Immerse Test showed an increase in sample mass of 1.04%, 1.1%, 1.05% and 1.14% respectively. FTIR test results did not show any new functional groups in the composite. The results of the SEM test indicated the presence of Na and Cl deposits on the sample surface as evidenced by the results of the EDS test that all samples contained Na and Cl elements. So that the weight gain occurs because the three materials are not chemically mixed which easily separate and cause cavities, these cavities are filled with HBSS liquid.